The Urgency Of The Formation Of Village Regulations Concerning Customary Institutions In Creating Legal Protection For The Adat Community Of Ngadisari Village Sukapura Sub-District Probolinggo District - Indah Dwi Qurbani; Muhammad Lukman Hakim; Tunggul Anshari S.N (Constitutionale, 2020)
The existence of customary institutions in the village is important because it has a duty to assist the Village Government and as partners in empowering, preserving and developing customs. The Village Customary Institution can occupy its rank with official recognition from the Government through a Village Regulation. Ngadisari Village was chosen as the object of this research because it has its own uniqueness, this village has indigenous people who are still strong in maintaining the traditions of their ancestors' heritage. Meanwhile, Ngadisari village also has a customary institution that carries out customary functions and is part of the original village structure that grows and develops on the initiative of the village community. The research method used is a type of empirical research and using sociological approach. The order of village regulations regarding customary institutions in order to make Adat Institutions as an alternative to dispute resolution, maintain local culture and play a role in village development. In addition, this formalization effort is also needed to maintain the existence of customary villages, provide legal protection and help cooperation between traditional village institutions of Ngadisari and other village customary institutions. This is in accordance with the duties of the customary institutions in Permendagri Number 18 of 2018 concerning Village Community Institutions and Village Traditional Institutions.